Rancang Aplikasi Perpustakaan Digital Universitas PGRI Silampari Berbasis Mobile Dengan Metode Prototype - Lastri Sartika; Rahman Dzaky Faishal Ali; Tia Julita; M.Rizki Syawaldi (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
The acceleration of information technology in the contemporary digital epoch necessitates higher education institutions to undergo continuous transformation to reinforce the quality of academic services, particularly within library management systems as central hubs for literature. Currently, Universitas PGRI Silampari encounters significant operational hurdles in its conventional book circulation management. Primary challenges encompass physical storage constraints for collections, inefficient reference retrieval mechanisms, and accessibility barriers for students with high mobility. These circumstances directly result in diminished academic productivity and prolonged administrative processing durations. This research initiates the design and development of an innovative mobile-based digital solution titled "i-Pustaka." The application is projected to optimize library service functionality and empower students to browse bibliographic data and execute borrowing transactions autonomously via smartphones. The system development strategy implemented is the prototype method, which facilitates adaptive and gradual design evolution through continuous evaluation cycles based on direct user feedback in the field. Primary data collection was conducted through participatory observation and in-depth interviews with library management, while secondary data were obtained through credible literature reviews. System construction utilizes an object-oriented paradigm, comprehensively visualized through use case, activity, and class diagrams. The research findings confirm that the integration of the "i-Pustaka" application provides seamless service access, transcending geographical boundaries and campus operational time constraints. This platform is empirically proven to expedite the book collection search duration and enhance the accuracy of administrative data management compared to previous manual systems. In conclusion, the development of i-Pustaka serves as a strategic instrument that not only offers practical solutions for circulation constraints but also significantly contributes to realizing the vision of modern academic service digitalization within the Universitas PGRI Silampari environment.